Relationship Between Vascular Endothelial Growth Factor Expression and Gleason Score in Prostate Carcinoma - Fadillah; Heni Maulani; Nursanti Apriyani (HM Publisher, 2021)
Prostate cancer is the most common cancer in men worldwide and ranks second in the Laboratory of Anatomical Pathology, Dr. Mohammad Hoesin with the highest incidence, especially at the age of more than 60 years. Factors that play a role as a prognostic factor and therapy in prostate carcinoma, including VEGF. The role of VEGF expression in prostate carcinoma as a prognostic and histopathological factor which is an important predictor for the progression of prostate carcinoma. This study aims to determine the relationship between VEGF expression and Gleason score in prostate carcinoma. This study was a cross-sectional observational study. Thirty samples diagnosed with prostate denocarcinoma were derived from the results of the tranurethral resection of the prostate (TRUP) and prostatectomy. Samples were taken from the archives in the Anatomic Pathology section of Dr. Mohammad Hoesin Palembang (period January 1, 2011 to December 31, 2013. Then the sample was stained with VEGF antibody, identified and analyzed the VEGF relationship with the Gleason.z score. The positivity of VEGF expression in prostate adenocarcinoma tended to be more prevalent in the Gleason score group ≥ 7 (43.3%) than in the Gleason score group <(10%). There was no significant relationship between VEGF expression and high Gleason score (p> 0.05). There was no significant relationship between VEGF expression and Gleason score in prostate adenocarcinoma